2014
DOI: 10.4103/0019-5049.135040
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided peritubal infiltration of 0.25% Bupivacaine versus 0.25% Ropivacaine for postoperative pain relief after percutaneous nephrolithotomy: A prospective double blind randomized study

Abstract: Background and Aim:Percutaneous nephrolithotomy (PCNL) is a common for managing renal calculi. Pain in the initial post operatie period is relieved by infiltration of local anaesthetic around the nephrostomy tract. We aimed to compare the analgesic efficacy of bupivacaine and ropivacaine.Methods:A total of 100 adult patients undergoing elective PCNL—under balanced general anaesthesia were randomly divided into bupivacaine group (Group B) and ropivacaine group (Group R). After completion of procedure, 23G spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…A two-sided P-value of <0.05 was considered statistically signi cant. P<0.01 was considered signi cant when multiple comparisons were performed for pain scores at rest and movement Previous studies detected a 40% difference in VAS score between the study groups, which is the primary outcome in our study [10,11], G* power computer program version 3.1.9.2 was used to calculate the sample size required with 80% power, an alpha error of 0.05 and allocation ratio of 1. [13] A sample size of 37 patients was calculated per group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A two-sided P-value of <0.05 was considered statistically signi cant. P<0.01 was considered signi cant when multiple comparisons were performed for pain scores at rest and movement Previous studies detected a 40% difference in VAS score between the study groups, which is the primary outcome in our study [10,11], G* power computer program version 3.1.9.2 was used to calculate the sample size required with 80% power, an alpha error of 0.05 and allocation ratio of 1. [13] A sample size of 37 patients was calculated per group.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound guided QL block has been described by Blanco as posterior extension of TAP Block to provide sensory block from T4-L2 [16]; later, it was used effectively by Sindwani et al [17]; to provide post laparoscopic nephrectomy. Peritubal or subcutaneous in ltration of the LA along the nephrostomy tube was used effectively as part of the PCNL postoperative analgesic strategy [10,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory block with Ropivacaine is similar to Bupivacaine (8) but Ropivacaine showed greater separation of sensory and motor block (9), (10) and better patient satisfaction (11) . Studies have also showed that Ropivacaine is effective for intraoperative and postoperative analgesia in patients undergoing PCNL (12), (13), (14) .…”
Section: Introductionmentioning
confidence: 99%